Implementing Cisco UCS Solutions. - Ahmed, Farhan (Professional expertise distilled, 2013)
A tutorial-based approach which will help you understand the practical methodologies and deploying of Cisco UCS components. If you are a professional such as a system, network, or storage administrator who is responsible for Cisco UCS deployments, this is the perfect book for you. You should have some basic knowledge of the server's architecture, network, and storage technologies. Familiarity with virtualization technologies is also recommended (though not necessary) as the majority of real-world UCS deployments run virtualized loads. Knowledge of Nexus OS is not necessary as the majority of th.